PERFORMANS COVER CROPS HIJAUAN PAKAN TERHADAP LEVEL PUPUK BOKASHI DAN KEPADATAN POPULASI - Kaligis, David A.; Dompas, Fredy (Universitas Sam Ratulangi, 2018)
RESPONS OF FORAGES COVER CROPS ON LEVEL OF ORGANIC FERTILIZER BOKASHI AND PLANT POPULATION DENSITY. The objectives of this research was to asses the interaction of bokashi levels and plant population density on vegetative growth of sorghum Brown Midrib (BMR) and Leucaena leucocephala legume trees. Level bokashi were LB1 = 0 G; LB2 = 200 G; LB3 = 400 G and LB4 = 800 G pot-1 interact with plant population density of KP1 = 2 plants; KP2 = 4 plants and KPB3 = 6 plants pot-1 of BMR, and for Lamtoro plant density were KP1= 1 plat, KP2= 2 plant, KP3= 3 plant and KP4 = 4 plant pot-1. Treatments were arranged in a 4 x 3 factorial with 3 replications based on a Completely Randomized Design. Variable measured were leaf length of leaf, number of leafes and plant height. The results showed that the interaction of both treatment had significant effect on leaf length (P<0.05), but did not have significant effect (P>0,05) on number of leafs and plant height of BMR. On the otherhand the optimum plant density was 3 plant per pot. Based on this results can be concluded that to get optimal vegetative growth of sorghum BMR needs bokashi fertilizer by 400 G/polybag at density of 2 plants/polybag, but up to 3 plant per pot for lamtoro.Keywords:Bokashi level of chicken manure, plant population density level, growth sorghum, growth.